Oleander - Zerbst, Fiona (Book collections on Project MUSE., 2009)
Oleander explores life's complexities, both beautiful and poisonous-love, death, art, the aftermath of war and genocide, travel, religion, revelation. More wide-ranging than Zerbst's previous volumes, Oleander charts experiences through which the self may be transformed.